Comparative Dosimetric Analysis of IMRT and VMAT in Head and Neck Cancers - Rawal, Trilok; Sharma, Neeti; Gajraj, Vikash Kumar; Meena, Ravi; Thanvi, Shubhangi; Singh, Guman; Jakhar, Shankar Lal; Kumar, H S (Asian Pacific Journal of Cancer Care, 2024)
Objective: This study aimed to dosimetrically evaluate and compare intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) plans for the irradiation of local head and neck cancers. The focus was on target coverage, conformity index, homogeneity index, and dose received by organs at risk (OARs). Material and methods: This prospective study was conducted on 50 patients randomly divided into two groups: one receiving IMRT plans and the other receiving VMAT plans. Results: PTV coverage was similar for both techniques. The conformity index was significantly higher for VMAT compared to IMRT. The homogeneity index was also better in VMAT plans than IMRT, except for higher PTV volumes where IMRT plans showed better results. The mean dose to parotid glands was significantly lower in VMAT plans. Additionally, the point maximum dose to the spinal cord, brainstem, and vestibulocochlear nerve was lower in VMAT plans. No significant difference was observed in the dose received by the spinal cord between the two arms. Conclusion: Based on the findings of this study, VMAT provides superior dose conformity, more homogeneous target coverage, and improved OAR sparing compared to IMRT in head and neck cancer treatment.